The generalized Lorenz-Mie theory and its identification with the dipole theory of forces for particles with electric and magnetic properties. (April 2022) - Ambrosio, Leonardo A.; de Angelis, Vinicius S.; Gouesbet, Gérard
Highlights: The dipole limit of the GLMT is investigated for particles having magnetic and electric properties. The role of non-standard forces is now revealed for pure magnetic and magneticelectric coupling forces. We succeed in establishing a full identification between the dipole limit of the GLMT and the dipole theory of forces. This work completes a previous investigation on the derivation of non-standard forces in the GLMT for arbitrary-index dipolar particles. Abstract: Complementing a previous work on optical forces and optical force categorizations on dipole particles having both electric and magnetic properties in the generalized Lorenz-Mie theory (GLMT), the present work provides a rigorous identification between the dipole limit of the GLMT and the dipole theory of forces (DTF) as applied to such particles. Since non-coupled force contributions from pure electric dipoles have already been recently investigated by the authors, here we focus on pure magnetic non-coupled and electric-magnetic coupling forces, the former being identified by means of the T -transformation recently presented by the authors, while the latter uses reduced partial wave expansions of the GLMT - derived during previous analysis of pure electric forces - to express the incident fields in the DTF in terms of beam-shape coefficients.